Plasma Membrane Origin of the Steroidogenic Pool of Cholesterol Used in Hormone-induced Acute Steroid Formation in Leydig Cells - Venugopal, Sathvika (J Biol Chem, 2016)
Hormone-sensitive acute steroid biosynthesis requires trafficking of cholesterol from intracellular sources to the inner mitochondrial membrane. The precise location of the intracellular cholesterol and its transport mechanism are uncertain. Perfringolysin O, produced by Clostridium perfringens, binds cholesterol. Its fourth domain (D4) retains cholesterol-binding properties but not cytotoxicity. We transfected steroidogenic MA-10 cells of mouse Leydig cell tumors with the mCherry-D4 plasmid. Tagged D4 with fluorescent proteins enabled us to track cholesterol. The staining was primarily localized to the inner leaflet of the plasma membrane and was partially released upon treatment with dibutyryl-cAMP (Bt(2)cAMP), a cAMP analog. Inhibitors of cholesterol import into mitochondria blocked steroidogenesis and prevented release of D4 (and presumably cholesterol) from the plasma membrane. We conclude that the bulk of the steroidogenic pool of cholesterol, mobilized by Bt(2)cAMP for acute steroidogenesis, originates from the plasma membrane. Treatment of the cells with steroid metabolites, 22(R)-hydroxycholesterol and pregnenolone, also reduced D4 release from the plasma membrane, perhaps evidence for a feedback effect of elevated steroid formation on cholesterol release. Interestingly, D4 staining was localized to endosomes during Bt(2)cAMP stimulation suggesting that these organelles are on the route of cholesterol trafficking from the plasma membrane to mitochondria. Finally, D4 was expressed in primary rat Leydig cells with a lentivirus and was released from the plasma membrane following Bt(2)cAMP treatment. We conclude that the plasma membrane is the source of cholesterol for steroidogenesis in these cells as well as in MA-10 cells.